Legal Protection of The Executory Rights of Separatist Creditors as Holders of Material Guarantees in Credit Agreements in The State of Bankruptcy Debtors - Inggrid Kusuma Dewi; Muhammad Arifin; Ida Nadirah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study examines the legal protection of the executorial rights of separatist creditors as holders of security rights in credit agreements when the debtor is declared bankrupt. As separatist creditors possess preferential rights over certain collateral objects, the implementation of their executorial rights often faces legal and procedural challenges in bankruptcy proceedings. The research analyzes the legal framework provided by Indonesian bankruptcy law, particularly concerning the position and priority rights of secured creditors. It also evaluates judicial practices and obstacles encountered during the execution of collateral. The findings highlight the importance of strengthening legal certainty and protection for secured creditors to ensure the fair enforcement of their rights without undermining the principles of bankruptcy distribution and debtor rehabilitation. Recommendations are proposed to harmonize the execution process with creditor protection mechanisms in insolvency law.